The National Science and Technology Library: A Chinese Model of Collaboration - Bao Xue-Ming (Issues in Science and Technology Librarianship, 2005)
Provides an overview of the National Science and Technology Library (NSTL). Establishment of the NSTL; Collection scope of the NSTL; Implications of NSTL for China.